Tomoelastography of the prostate using multifrequency MR elastography and externally placed pressurized-air drivers - Dittmann, Florian; Reiter, Rolf; Haas, Matthias; Asbach, Patrick; Fischer, Thomas; Braun, Juergen; Sack, Ingolf; Guo, Jing (Magnetic Resonance in Medicine, 2018)
Purpose: To demonstrate the feasibility of in vivo multifrequency magnetic resonance elastography (MRE) of the prostate using externally placed drivers. Methods: Three pressurized-air drivers were used to excite shear waves within the prostate at vibration frequencies of 60, 70, and 80 Hz. Full 3D wave fields were acquired by multislice spin-echo echo-planar imaging in conjunction with tomoelastography wave speed recovery for generating full field-of-view stiffness maps. Twelve healthy volunteers were repeatedly scanned to analyze test–retest reproducibility. Five patients with suspected prostate cancer were investigated to demonstrate the clinical feasibility of the method. Results: In healthy volunteers, the shear wave speed of the entire prostate was 2.24 ± 0.20 m/s with a repeatability coefficient of 0.14 m/s and 88% intraclass correlation coefficient. No significant difference between the peripheral zone (2.27 ± 0.20 m/s) and the central gland (2.22 ± 0.23 m/s) was observed. In patients, wave-speed maps displayed stiff regions consistent with the localization of suspicious masses detected by other imaging markers. Conclusions: The proposed method provides reproducible quantitative maps of tissue stiffness throughout the pelvic region and can easily be integrated into clinical imaging protocols. Clinical stiffness maps display many details of potential interest for cancer diagnosis. Magn Reson Med 79:1325–1333, 2018. © 2017 International Society for Magnetic Resonance in Medicine.
CRIS-Team Scopus Importer:2022-08-03
Keywords: multifrequency magnetic resonance elastography (MRE); multiparametric MRI; noninvasive; prostate carcinoma; shear waves; tomoelastography